Analisis Kesalahan Kaidah Kebahasaan dalam Media Publikasi di Kota Medan : Penyebab dan Solusinya - Ita Khairani; Olivia Febriana Gea; Khayla Akmal Panjaitan; Cinta Febby Dewita; Inda Wati Manik; Ferdinan Saragih (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to analyze language errors found in public media such as banners, posters, and billboards in Medan City. The errors analyzed include morphological, phonological, syntactic, lexical, and spelling mistakes that do not align with the Indonesian Language Spelling System (PUEBI) and the Indonesian Dictionary (KBBI). The method used is qualitative descriptive, with data collection through direct observation of public media in various locations in Medan City. The results show that language errors are generally caused by a lack of understanding of correct language rules, limited knowledge, and the use of everyday language mixed with colloquial or regional languages. The proposed solutions to address these issues are providing training for media creators, creating clearer language guidelines, and utilizing language technology for automatic spelling checks. The implications of this study are to raise public awareness about the importance of using proper and accurate Indonesian in public media, to support effective communication, and to avoid miscommunication.